Association of Helicobacter pylori infection with the risk of neurodegenerative disorders: a systematic review and meta-analysis - Jiwen Du; Weiting Shen; Zhenting Zhou; Qiuyan Wu; Zongyao Ai (Frontiers in Medicine)
ObjectiveThe pathogenesis of neurodegenerative diseases is complex, involving multiple factors, including genetic, environmental, and lifestyle elements. Recent studies have suggested that infectious agents may act as important triggers for neurodegenerative diseases. This study aimed to evaluate the association between Helicobacter pylori (H. pylori) infection and the risk of neurodegenerative disorders through a systematic review and meta-analysis of existing literature.MethodsA systematic search was conducted across the PubMed, Embase, and Cochrane Library databases for studies published up to December 2024. The combined effect sizes were expressed as odds ratios (OR) with 95% confidence intervals (CI) and were calculated using a random-effects model. Further exploratory analyses included sensitivity analyses, subgroup analyses, and assessment of publication bias.ResultsForty-one studies involving 159,220 participants were selected for the meta-analysis. We found that H. pylori infection was associated with an increased risk of Parkinson’s disease (OR: 1.70; 95% CI: 1.36–2.13; p < 0.001), all-cause dementia (OR: 1.56; 95% CI: 1.24–1.96; p < 0.001), and Alzheimer’s disease (OR: 1.43; 95% CI: 1.01–2.02; p = 0.045). However, H. pylori infection was not associated with the risk of multiple sclerosis (OR: 0.81; 95% CI: 0.59–1.11; p = 0.193). Sensitivity analysis suggested that H. pylori infection might play a protective role in the subsequent risk of multiple sclerosis. Subgroup analyses indicated that the association between H. pylori infection and neurodegenerative disorders may vary based on country, study design, H. pylori detection technique, and study quality.ConclusionThis study found that H. pylori infection may be associated with an elevated risk of Parkinson’s disease, all-cause dementia, and Alzheimer’s disease.Systematic review registrationINPLASY (INPLASY202510044).